„Disparater Tausch“: Diamanten, Öl und Bürgerkrieg in Afrika - Custers, Peter (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
Financing civil wars in Africa depends of the export of raw materials like diamonds or oil as well on the side of government as on the side of rebels. Transnational corporation get big profits by these exports, especially in the monopolised sector of diamond industries. In result, there exists not only an “unequal exchange” because of bad terms of trade, but a “disparate exchange”: natural wealth is exchanged against waste products like weapons and the use of these weapons leads to further destruction and misery.